Pengaruh kepemimpinan dan komitmen kerja terhadap kinerja pegawai satuan polisi pamong praja propinsi Riau - Andi Nofrianto; Dewita Suryati Ningsih; Marzolina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to determine the effect of variables simultaneously and partially leadership , commitment to the performance of work Civil Service Police Unit of Riau Province . The research was conducted at the Civil Service Police Unit Riau Province is located on the road Lieutenant Colonel Hasan Basri Pekanbaru.In this study population studied were all employees of Civil Service Police Unit of Riau province , amounting to 325 people . Sampling method used was disproportionate strafied random sampling method, then using the Slovin then obtained a sample of 100 people.Linear Regression method is to determine the relationship between the dependent variable (Y) with the independent variable (X) is used as the data analysis necessary to first examine the validity and reliability of research data . The results showed that there was a significant effect of both simultaneously and significantly between the variables of leadership , commitment to the work performance of employees Civil Service Police Unit of Riau Province . Work commitment variable is the dominant variable in affecting the performanceof the Civil Service Police Unit employees Riau Province. With the expected leadership and commitment to work can be a key factor to improve the performance of the Civil Service Police Unit employees Riau Province to further increase employee self-actualization .Keywords : Leadership , work commitments , Performance